Impact of ESG Disclosure on Stock Returns: Evidence from Egyp Firms with Tax and Governance Effects - Hussainey, Abobaker; Umayah, Zahran; Uzmany, Hafez; R, Ismail (Journal Economic Business Innovation, 2025)
Purpose: This study aims to examine the effect of environmental, social, and governance (ESG) disclosure on stock returns with the moderating effect of tax rate, family ownership and foreign board members in Egypt between 2020 and 2024.Methods: Using a panel of 735 firm-year observations for the top 100 Egyp firms listed on the EGX, the study employs ordinary least squares (OLS) regression together with industry- and year-fixed effects. The analysis controls for size, profitability, leverage, and capital intensity at the firm level.Results: The results indicate that ESG disclosure is positively and significantly related to return (β2 = 0.169), which means that stronger ESG disclosure is connected with better stock performance. Furthermore, tax rate (ETR) has a negative influence on ESG disclosure, and family and foreign board members positively influence the ESG disclosure.Novelty: This is the first study that provides insights into the determinants of ESG disclosure in an emerging market (Egypt) and the economic implications.Implications: These findings underscore the need for ESG transparency for investors and policymakers, and the role of governance in enabling sustainable financial performance